The essay in literature - Patten, John Vernon (My University, 1895)
Introduction: There is probably no other term in English literature, which is used so indiscriminately, or in such an ambiguous sense, as the term “essay.” It is usually applied to any short argumentative or expository discourse in prose; yet in its tone meaning it need be neither short, argumentative nor expository. The word is in many ways synonymous with the word “attempt,” and properly consists in nothing more nor less than an accumulation of ideas upon a certain topic, clearly and correctly stated in a manner intended to force the reader’s attention. It is usually, though not necessarily, short, since in prolixity there is waste of strength. The human mind though very comprehensive has its limits of endurance beyond which it is useless to transcend. Probably it is to its brevity, “point,” and unconventionality of style that the essay owes its success in literature, for certainly no literary form ever rose at a more auspicious time, advanced with more rapidity or wrought a more lasting and important work than it.
Citation: Patten, John Vernon. The essay in literature. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Literature; Essay; Theses; Manuscripts (documents)